Penggunaan Nas Hadith Dalam Kempen Zakat Lembaga Zakat Negeri Kedah - Muhammad Yusry Affandy bin Md Isa; Zulhimi bin Mohamed (Penerbit USIM, 2024)
PAPER PROCEEDINGS: THE 9TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION SWAT 2023: “AL QURAN AS A SOURCE OF REVELATION IN BUILDING A CIVILIZED SOCIETY”/ Edited by : Dr. Nadiah Ramlan, Dr. Irwan Santeri Doll Kawaid, Dr. Kauthar Abd Kadir, Nurfatin Nazilah Zainol 4th – 5th October 2023 / 19-20 Rabiul Awal 1445H I Faculty of Quranic and Sunnah Studies